Current Research in Pharmacy and Pharmaceutical Sciences II-2024 - Said, Saja; Özbey, Gül; Altun, Beril; Dedeoğlu, Nurcan; Tugrak Sakarya, Mehtap; Özmen Özgün, Dilan; Aksoy, Dilek; Çinar, İrem and Özakar, Emrah and Sevinç Özakar, Rukiye and Özmutlu, Muhammet Enes and Özakar, Emrah and Öztürk Karagöz, Berna (Academician Publishing Book DOI Portal, 2024)
-